Independent Television Production in the UK From Cottage Industry to Big Business - Lee, David (Springer International Publishing, 2018)
This book is the first authoritative account of the UK's independent television production sector, following the creation of Channel 4 in 1982. It examines the rise of a global industry, increasingly interconnected through format development, distribution, ancillary sales and rights. Drawing on case studies, interviews and policy analysis; the author considers the cultural politics behind the growth of the 'indies', the labour conditions for workers in this sector, and some of the key television programmes that have been created within it. Filling an important gap in our understanding, this book constitutes a comprehensive account of this vital cultural industry for students, academics and researchers working in the areas of the cultural and creative industries, media and cultural policy and television studies.